Adaptation of optimization algorithm parameters to reconstruction of chaotic attractor - Drūlytė, Miglė; Lukoševičiūtė, Kristina; Mekšunaitė, Erika (Lietuvos matematikos rinkinys, 2015)
Optimal selection of time delay for time series reconstruction is an important problem in time series analysis and forecasting. When reconstructing the time series into phase space with non-uniform time delay, a time delay selection becomes a difficult optimization problem. To solve this problem, this paper presents two optimization algorithms: cuckoo search algorithm and artificial bee colony optimization algorithm.